Composition and Density of Gastropode in Mangrove Habitat of Banyuurip, Ujung Pangkah - Gresik - Arifianti, Eka Nur; Latuconsina, Husain; Zayadi, Hasan (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research was conducted in Banyuurip Mangrove Center (BMC), Ujung Pangkah-Gresik during July-August 2020. Determination of the observation station purposively based on physical differences in mangrove habitat. Estimation of mangrove and gastrode density by systematic sampling method using belt transects. There were 12 mangrove species with the highest number of species in the coastal mangrove habitat, with the highest species composition and density of Avicennia marina. The highest mangrove density was found in coastal mangrove habitats for all criteria. The number of gastropods found were 2,171 specimens belonging to 15 species, 5 families and 5 orders. The highest number of species, families and orders in coastal mangrove habitat were 1,191 specimens, 11 species from 5 families and 5 orders, the lowest was in estuarine mangrove habitat as many as 980 specimens from 9 species, 2 families and 2 orders. Densities of gastropods differ between mangrove habitats, with the highest density in coastal mangrove habitats and the lowest in estuarine mangrove habitats. The composition and density of the highest gastropods species in the estuary mangrove habitat is Cassidula aurisfelis and in the coastal mangrove habitat is Pirenella cingulata.